Artificial Intelligence (AI) Technology in Educational Transformation to Improve Student Intelligence in the Era of Disruption - Hidayati, Hidayati (Yayasan Meira Visi Persada, 2025)
Artificial Intelligence (AI) technology in the Disruption era is developing rapidly. The aim of this article is that Artificial Intelligence (AI) technology in Educational Transformation will have an impact on making Indonesia progress in the Disruption era. The methodology in this article is a qualitative descriptive method with a literature study approach. The question is how to prepare adequate equipment to support the success of educational transformation through Artificial Intelligence (AI) technology in the Disruption era? How is the mechanism of preparing schools and teachers to face technological developments in the Disruption Era using Artificial Intelligence (AI) technology? The research results show that the Disruption era has affected all aspects of human life, both economic, political, sociocultural, ethical, religious, and even the world of education. The Covid-19 pandemic has significantly changed almost every aspect of human life around the world. Schools need to integrate curricula that follow the latest developments in various fields of science, such as Artificial Intelligence (AI), artificial intelligence, data science, and the latest technology. This disruption era can replace old physical technologies with new digital technologies to produce something new that is more useful and efficient. Curriculum based on Outcome Based Education (OBE) results for teachers can be achieved through clear and measurable learning, relevant, sustainable and adaptive performance-based assessments